UMKM Go Digital: Building Competitiveness through Digital Literacy in Tunggulsari Village and Introduction to Halal - Dwi Astuti Wahyu Nurhayati; Ahmad Bin Efendi; Sergio Adorno (Kerigan: Jurnal Pengabdian Masyarakat, 2023)
Purpose: This community service program was designed to strengthen the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Tunggulsari Village by enhancing digital literacy and raising awareness of halal certification. The program responds to the low digital adoption and limited knowledge of product legality that hinder the growth of rural MSMEs. Method: The program applied the Asset-Based Community Development (ABCD) approach, emphasizing the identification and mobilization of community assets. Implementation included asset mapping, focus group discussions, collaborative planning, a seminar on digital literacy and halal certification, as well as pre–post knowledge assessments, questionnaires, and follow-up monitoring. Practical Applications: The results showed significant improvement in participants’ digital readiness, with WhatsApp Business adoption increasing from 10% to 60% and Instagram usage from 5% to 45%. A total of six MSME actors declared readiness to pursue halal certification, and two formally submitted documents to the Halal Product Assurance Organizing Agency (BPJPH). The program also initiated the idea of establishing a UMKM Digital Center to serve as a local hub for mentoring and certification advocacy. Conclusion: The integration of digital literacy training with halal certification awareness, framed within the ABCD approach, proved effective in fostering participatory and sustainable empowerment. The program not only enhanced MSME knowledge and practices but also provided a replicable model for rural MSME development. Embedding such initiatives into broader government policies and long-term campus–village collaborations will ensure sustainability and scalability in strengthening MSME competitiveness in Indonesia’s digital economy.